2016
DOI: 10.7287/peerj.preprints.2370v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regional drivers of clutch loss reveal important trade-offs for beach-nesting birds

Abstract: Coastal birds are critical ecosystem constituents on sandy shores, yet are threatened by depressed reproductive success resulting from direct and indirect anthropogenic and natural pressures. Few studies examine clutch fate across the wide range of environments experienced by birds; instead, most focus at the small site scale. We examine survival of model shorebird clutches as an index of true clutch survival at a regional scale (~ 200 km), encompassing a variety of geomorphologies, predator communities, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…It is also possible that red foxes in our study area are not influenced by anthropogenic features or the levels of human presence within the study area. Maslo et al (2016) reported that predation of nests was not stronger on human‐dominated beaches, suggesting that habitat use by predators was not strongly influenced by human activity.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that red foxes in our study area are not influenced by anthropogenic features or the levels of human presence within the study area. Maslo et al (2016) reported that predation of nests was not stronger on human‐dominated beaches, suggesting that habitat use by predators was not strongly influenced by human activity.…”
Section: Discussionmentioning
confidence: 99%
“…Results do not differ if we instead analyze each trait separately as a response variable in a linear mixed-effect model with capture method as the sole fixed effect and capture site, order of use of capture methods, and/or order of stimulus presentation (for behavioral data) as random effects. Conditional inference tree and other decision tree approaches are increasingly being used in ecological research (e.g., Johnstone, Lill & Reina, 2014;Maslo et al, 2016;Burke et al, 2020;d'Entrement et al, 2020), and can be preferable to traditional regression methods as they can allow for a more conservative, refined, and holistic approach to identifying differences among groups (Cutler et al, 2007;Müller, Schröder & Müller, 2009, Blank & Blaustein, 2014. Conditional inference trees are also powerful because of their ability to simultaneously assess categorical and continuous variables (including data with non-normal distributions) and to accommodate missing values (Hothorn, Hornik & Zeileis, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Corvids are intelligent, efficient predators that are also highly adaptable (Maslo et al 2016). Having a suite of effective methods to decrease their predation rates is important for seabird colony management.…”
Section: Management Implicationsmentioning
confidence: 99%
“…In a quantitative assessment of the main threats to seabirds, Dias et al (2019) determined that predation from invasive alien and other problematic species are one of the greatest threats to seabird persistence. Corvids have been identified as one of the most important seabird egg predators because they are intelligent, mobile, and their density increases with proximity to humans (Maslo et al 2016). Intense corvid predation has been linked to the complete abandonment of seabird colonies (Brunton 1999, Voigts 1999, Forys et al 2015), but even moderate predation can delay nesting and decrease productivity.…”
mentioning
confidence: 99%